Effects of (-)-stepholidine on NMDA receptors: comparison with haloperidol and clozapine - Gu Wei-hua; Yang Shen; Shi Wei-xing; Zhen Xue-chu; Jin Guo-zhang (Acta Pharmacologica Sinica, 2016)
Aim: To examine whether (-)-stepholidine (SPD) has a direct effect on the N-methyl-D-aspartic acid receptors (NMDAR) containing the NMDA receptor subunits NR2A or NR2B and to compare its effect with those of haloperidol (Hal) and clozapine (Cloz). Methods: NMDAR was transiently expressed in human embryonic kidney 293 (HEK293) cells. Changes in intracellular calcium concentration ([Ca2+]i) induced by NMDAR activation were monitored with Fura-2 ratio imaging techniques. Results: SPD had no significant effects on either subunit of NMDAR at a concentration of less than 100 μmol/L. Hal selectively inhibited NMDAR containing the NR2B subunit, whereas Cloz inhibited both subunits of NMDAR Although both Hal and Cloz inhibited NR1a/NR2B receptor-mediated Ca2+ influx, their effects were different. Hal was more potent and had a faster peak effect than Cloz. Conclusion: Both Hal and Cloz inhibit NMDAR-mediated function, Whereas SPD produced only a little inhibition at a high concentration. Based on our other studies, the modulation of SPD on NMDAR function may be via D1 receptor action underlying an indirect mechanism.